Discovering Efficient Method Extracting Arsenic from Human Milk Samples (International Journal of Innovative Research in Engineering & Management, 2023)
In this article, the arsenic levels in  drinking water were investigated. Hair and nail arsenic is  strongly related, however, according to principal  component analysis (PCA). According to our findings,  lactating women with hypertension higher levels. Arsenic  levels in infants' blood, nails, and urine were examined,  and the findings indicated a substantially high body burden  of arsenic in regions. The hair and nail arsenic levels were  shown to beage-dependent utilizing PCA. The methods  for extracting arsenic from human milk samples are  effective in both literatures. These results would help in the  development of a faster and more efficient technique for  removing arsenic from milk samples. Although the  procedure will take longer than anticipated, it does not exceed 5-6 hours. Furthermore, such studies reveal the  degree of arsenic exposure in individuals living in  complicated settings. People are exposed to less arsenic as  a result of this, which may lead to severe cases of chronic  arsenic poisoning. Prenatal exposure to babies may  possibly cause genetic abnormalities as well as physical  and mental problems.
Keywords: Arsenic Levels; Drinking Water; Human Milk; Samples; Skin Lesions; West Bengal